The Seddling Growth of Nyatoh (Palaquium spp.) on PT. Antam’s Tailing Media Business Unit of Pongkor in Addition of Coconat Shell Charcoal and Bokashi Compost - Basuki Wasis; Hafiizh Baskara (Jurnal Silvikultur Tropika, 2013)
Sludge of  gold mining  is one of main toxic sludge toward environment because level of high  acidity, so that can damage soil fertility and local vegetation  as impact from toxicity and contaminant of  food chain. That characteristic of tailing can cause problems in revegetation activity, so needing an effort for land repairing with adding coconut shell charcoal and bokashi compost fertilizer before a revegetation effort. Cococnut shell charcoal and bokashi compost fertilizer can repair soil condition that is poor of nutrients as a nutrient source and microbe  for soil fertility. Beside that, an effort that need to be conducted is selection of appropiate  plant species. Nyatoh (Palaquium spp) is one of local plant in Indonesia that can be recomended to be devoleped in revegetation effort at ex-mine area.